2020
DOI: 10.1038/s41598-020-73454-w
|View full text |Cite|
|
Sign up to set email alerts
|

Hypervirulent pneumococcal serotype 1 harbours two pneumolysin variants with differential haemolytic activity

Abstract: Streptococcus pneumoniae is a devastating global pathogen. Prevalent in sub-Saharan Africa, pneumococcal serotype 1 is atypical in that it is rarely found as a nasopharyngeal coloniser, yet is described as one of the most common causes of invasive pneumococcal disease. Clonal sequence type (ST)-306 and ST615 are representative of the two major serotype 1 lineages A and C, respectively. Here we investigated the virulence properties and haemolytic activities of these 2 clonal types using in vivo mouse models and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…Sequencing of the pneumolysin gene confirmed that this strain harboured a non-haemolytic pneumolysin. Non-haemolytic pneumolysin has been found to be associated with meningitis outbreaks in serotype 1 and has already been reported in recent publications in serotype 8 strains (Kirkham et al, 2006;Jefferies et al, 2007;Panagiotou et al, 2020). Although the serotype 8, ST53, strain had no haemolytic activity, we found it produced large quantities of pneumolysin, as seen with serotype 1 strains with increased pathogenicity (Jacques et al, 2020).…”
Section: Figuresupporting
confidence: 78%
“…Sequencing of the pneumolysin gene confirmed that this strain harboured a non-haemolytic pneumolysin. Non-haemolytic pneumolysin has been found to be associated with meningitis outbreaks in serotype 1 and has already been reported in recent publications in serotype 8 strains (Kirkham et al, 2006;Jefferies et al, 2007;Panagiotou et al, 2020). Although the serotype 8, ST53, strain had no haemolytic activity, we found it produced large quantities of pneumolysin, as seen with serotype 1 strains with increased pathogenicity (Jacques et al, 2020).…”
Section: Figuresupporting
confidence: 78%
“…Zafar et al, showed that administration of recombinant PLY dose of 200 ng/day induced shedding of pneumococci and mucosal inflammation ( 35 ). Intranasal administration of PLY at 10 ng/g body weight (corresponding to 0.25 μg for 6-8 week mice) restored virulence of an avirulent ST306 pneumococcal clone expressing a non-cytolytic PLY variant ( 36 ). Based on the above studies, we tested two intranasal doses of 0.25 and 0.5 μg PLY, but we observed mortality at 0.5 μg dose.…”
Section: Resultsmentioning
confidence: 99%
“…This contrasts with the depletion of pneumolysin in an ST615 clone which renders the isolate completely avirulent in murine models of pneumonia [97]. The pore-forming ability of pneumolysin was described as a critical virulence factor for pneumococci [98].…”
Section: High Attack Rate Pneumolysin and Haemolytic Activitymentioning
confidence: 97%